Efektifitas senam lansia terhadap tingkat tekanan darah pada penderita hipertensi - Redo Nopris Pratama; Vitri Dyah Herawati; Indriyati Indriyati (Journal of Health and Therapy, 2025)
Hypertension is a leading contributor to morbidity and mortality in Indonesia and is influenced by multiple factors, including lifestyle and dietary patterns. Regular physical activity, such as older-adult exercise (senam lansia), may help counter functional decline and support blood pressure control. This study aimed to examine the effect of senam lansia on blood pressure among older adults with hypertension. A pre–post experimental design was used, with blood pressure measured before and after the exercise program at the Nusa Indah community health post (Posyandu). The mean pre-exercise systolic blood pressure was 159.75 mmHg and decreased to 153.45 mmHg after the intervention. The mean diastolic blood pressure declined from 101.15 mmHg pre-exercise to 94.85 mmHg post-exercise. Statistical testing indicated a significant effect of senam lansia on blood pressure among hypertensive older adults. In conclusion, senam lansia was effective in reducing blood pressure in older adults with hypertension at Posyandu Nusa Indah, Rejomulyo Village, Palas District, South Lampung Regency.